Design, synthesis, and conformational studies of [DOTA]‐Octreotide analogs containing [1, 2, 3]triazolyl as a disulfide mimetic. Issue 5 (14th May 2018) - Testa, Chiara; D'Addona, Debora; Scrima, Mario; Tedeschi, Anna Maria; D'Ursi, Anna Maria; Bernhard, Claire; Denat, Franck; Bello, Claudia; Rovero, Paolo; Chorev, Michael; Papini, Anna Maria
Abstract: Somatostatin (SS) is a cyclic tetradecapeptide able to inhibit the release of growth hormone (GH) mainly through the binding to two G‐protein coupled receptor (GPCR) subtypes, SSTR2 and SSTR5 . These receptors are overexpressed in approximately 90% of carcinoid tumors. However, the clinical use of somatostatin is limited by its short half‐life in vivo . In order to overcome this severe drawback, a huge number of analogs have been prepared, leading to the development of Octreotide, which is currently used in the clinic, among other applications, to treat various neuroendocrine tumors and, radiolabeled by, for example, 111 In, 11 C, and 68 Ga, for imaging SS‐secreting tumors. Despite the success of Octreotide, there is an unmet need for the development of novel, more stable and selective Octreotide‐derived radiotherapeutics. To this end, the Cu(I)‐catalyzed azide‐alkyne 1, 3‐dipolar Huisgen's cycloaddition, the prototypic click reaction, presents a promising opportunity to replace the susceptible disulfide bridge with a durable [1, 2, 3]triazolyl containing bridge and to introduce conformational constraints increasing specific receptor binding. Herein we report the design and synthesis of a series of i ‐to‐ i  + 5 1, 4‐ and 4, 1‐disubstituted [1, 2, 3]triazolyl‐bridged cyclopeptides derived from the Octreotide scaffold and their detailed conformational analysis via NMR spectroscopy. Abstract :